P9 Coronary artery calcification on thoracic CT is associated with pulmonary hypertension and is an independent predictor of mortality in systemic sclerosis. (21st September 2022) - Rossdale, Jennifer; Graby, John; Charters, Pia; Burnett, Tim; Harris, Maredudd; Jones, Calum; Greenish, Davyd; Bartlett, Jessica; Gilroy, Andrew; Sanghera, Jamie; Robinson, Graham; Pauling, John D; et al.
Abstract : Objective: Coronary artery calcification (CAC) on thoracic computed tomography (CT) is a known biomarker of coronary artery disease and mortality. Systemic Sclerosis (SSc) is a pro-inflammatory condition; microvascular inflammation is increasingly hypothesised to drive pulmonary hypertension (PH) in SSc. Inflammation is also a driver of CAD. We hypothesised that CAC would be prevalent and associated with mortality in SSc. Methods: Retrospective analysis of 262 CTs in SSc patients from a prospectively maintained clinical database at a tertiary Rheumatology/PH service March 2007-March 2021 (mean age 65±12, 14% male). 86/262 (33%) had interstitial lung disease (ILD), 128/262 (49%) had PH. CTs were re-reviewed for CAC; severity was graded by experienced readers using a four-point scale per vessel and summed for total CAC score (CACS). Results: CAC was present in 152/265 (57%). All-cause mortality occurred in 65/262 (25%) patients over mean 5±3 years follow-up. Presence of CAC was associated with >2 times risk of death (Hazard ratio [HR] 2.41; 95% CI 1.3–4.5; p=0.006), correcting for age and gender. PH was predictive of mortality (HR 3.6, 95%CI 1.4–9.3, p=0.007), corrected for age and gender; ILD was not (HR 1.3, 95% CI 0.8–2.2, p=0.34). PH was significantly associated with CAC (X 2 =7.7, p=0.009). In contrast, ILD had no significant association with CAC (X 2 =0.57, p=0.81). Conclusion: CAC is common in SSc and is associated with PH. PH and CAC are predictors of mortality in SSc and both have a hypothesised pro-inflammatory driver. Further validation is required to assess the potential role for anti-inflammatory therapies.